Error messages on learning Micro-CDS/ISIS the Philippine experience - Salang, Maria Maura C. (Institute of Library Science, University of the Philippines Diliman, 1992)
The purpose of this study is to evaluate the user friendliness of Micro-CDS/ISIS focusing error messages. Specifically, it seeks to find out the error messages that are frequently encountered. It also determines how clearly the error messages are understood and examines if having computer/programming exposure facilitates learning the software. It ends by citing the problems encountered and difficulties experienced by the users and recommending possible solutions and suggestions.